Essentials of autopsy practice : advances, updates and emerging technologies - Rutty, Guy N. (Springer London, 2014)
This book covers new and exciting topics which have emerged in the area of autopsy recently, including the three different post-mortem CT-angiography systems currently available to practitioners in this field; a highly topical chapter on the role of genetic abnormalities in the handling of drugs within the body and how this can affect the interpretation of toxicological results in relation to how the drug may have caused or contributed to death; an update on the current classification and considerations related to deaths due to hanging; a review of injuries and fatalities caused by animals including post-mortem scavenging; an authoritative review of poisons and toxins from water and the life that inhabits it; and recent advances in knowledge in the use of entomology as an investigative tool as well as knowledge related to colonisation of cadavers by insects, animals and birds.   Essentials of Autopsy Practice: Advances, Updates and Emerging Technologies is a multi-subject book, aimed at different grades of practitioners, from different practice areas, covering topics that are currently discussed and anticipated to be discussed in the field of autopsy practice over the next few years.